Evolução do hábito alimentar e utilização do substrato pelo gênero Philodryas Wagler, 1830 - Machado Filho, Paulo Roberto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Feeding behavior is a determining factor on the living habits of snakes, exerting a strong influence on the foraging substrate, for example. However, there are still gaps on the natural history and, consequently, on the evolutionary history of several genera and species of snakes, especially those included in the Dipsadidae family. The Philodryas genre has currently 21 valid species. Nevertheless, there is only a few species with a well detailed list of their diets; therefore, this study aims to compile and generate new information about use of the substrate use and diet, based on information from literature, zoological collections and unpublished records by South American researchers. A total of 1133 diet items were recorded: 902 from the literature, 199 of zoological collections and 32 observations of other researchers. Among the 21 valid species, Philodryas cordata, P. laticeps, P. livida, P. simonsii and P. tachymenoides were not studied, since there were no available specimens in the zoological collections consulted; Furthermore, P. livida was the only studied species with no diet items recorded. The species with the highest frequency of frogs in their diet was P. patagoniensis, while spiders were more frequent for P. agassizii, lizards for P. argentea, P. chamissonis and P. nattereri, and mammals for P. aestiva, P. baroni, P. mattogrossensis, P. olfersii, P. psammophidea, P. trilineata, P. varia and P. viridissima. The species P. patagoniensis was the only species of the genus that presented amphisbaena and fish in the diet. Few diet records were obtained for the species P. amaru, P. arnaldoi, P. cordata, P. georgeboulengeri, P. laticeps, P. simonsii and P. tachymenoides and so it was not possible to ascertain which food item groups are more common for these species. Regarding the use of substrate, P. argentea and P. viridissima have a high affinity for the arboreal substrate, P. georgeboulenge ...

O hábito alimentar é fator determinante sobre os hábitos de vida das serpentes, exercendo forte influência sobre o substrato de forrageio, por exemplo. No entanto, ainda existem lacunas sobre a história natural e, consequentemente, da história evolutiva de vários gêneros e espécies de serpentes, sobretudo as incluídas na família Dipsadidae. O gênero Philodryas apresenta, atualmente, 21 espécies válidas, entretanto poucas são as espécies que apresentam lista bem detalhada de sua dieta; por isso este trabalho tem como objetivo compilar e gerar novas informações de utilização de substrato e dieta, utilizando como base as informações provenientes da literatura, de coleções zoológicas e de registros não publicados por pesquisadores sul americanos. Foram contabilizados 1133 itens; destes, 902 são provenientes da literatura, 199 de coleções zoológicas e 32 de observações de outros pesquisadores. Dentre as 21 espécies válidas atualmente, não foram avaliados espécimes de Philodryas cordata, P. laticeps, P. livida, P. simonsii e P. tachymenoides por não constarem exemplares nas coleções zoológicas utilizadas neste estudo; além disso, a espécie P. livida foi a única que não obteve registros de dieta. A espécie que apresentou maior frequência de anuros em sua dieta foi P. patagoniensis, aranhas P. agassizii, lagartos P. argentea, P. chamissonis e P. nattereri, e mamíferos P. aestiva, P. baroni, P. mattogrossensis, P. olfersii, P. psammophidea, P. trilineata, P. varia e P. viridissima. A espécie P. patagoniensis foi a única espécie do gênero que apresentou anfisbenas e peixes na dieta. Foram obtidos poucos registros de dieta para as espécies P. amaru, P. arnaldoi, P. cordata, P. georgeboulengeri, P. laticeps, P. simonsii e P. tachymenoides e por isso não foi possível averiguar quais os grupos de item alimentares mais frequentes para estas espécies. Em relação a...
Keywords: Ecologia animal; Cobra; Animais - Alimentos - América do Sul; Animais - Comportamento; Historia natural